Potensi Antipiretik Ekstrak Metanol Herba Pugun Tanoh (Picria fel-terrae Lour.) pada Tikus Putih Jantan yang Diinduksi 2,4-Dinitrofenol - Romansa Sianipar; Vivi Asfianti; Debi Meilani (Yayasan Penelitian dan Inovasi Sumatera, 2026)
Background: Pugun tanoh herb (Picria fel-terrae Lour.) is a medicinal plant belonging to the family Scrophulariaceae and has traditionally been used to treat malaria, promote diuresis, relieve colic, reduce fever, and manage skin diseases. Objective: This study aimed to evaluate the antipyretic activity of the methanol extract of Pugun tanoh herb in male white rats (Rattus norvegicus) induced with 2,4-dinitrophenol and to determine the most effective dose. Methods: This experimental study used a digital thermometer to measure changes in the body temperature of rats. The extract was administered at doses of 50, 100, and 200 mg/kg body weight, with Na-CMC as the negative control and paracetamol at 20 mg/kg body weight as the positive control. Results: The results showed that the methanol extract of Pugun tanoh herb exhibited antipyretic activity. Doses of 50, 100, and 200 mg/kg body weight reduced the body temperature of rats, with mean temperatures of 37.416 °C, 36.776 °C, and 36.388 °C, respectively. Conclusion: The dose of 200 mg/kg body weight demonstrated the strongest antipyretic effect. This activity is presumed to be associated with the flavonoid content of Pugun tanoh herb.